Use of healthcare services preceding HIV diagnosis – missed opportunities for earlier diagnosis, Finland, 1996 to 2019 - Pia Kivelä (Eurosurveillance)
Background HIV testing based on indicator conditions is recommended to diagnose HIV earlier. Aim Our aim was to assess opportunities for earlier diagnosis of HIV. Method This is a retrospective study on people living with HIV (PLWH) included in the national HIV register. We collected data on public primary outpatient healthcare (PHC) (2011–2019), secondary and tertiary outpatient healthcare (STHC), and all inpatient care (1996–2019) from the Care Register for Health Care from the presumed acquisition, estimated by CD4+ T-cell count at diagnosis, until the diagnosis of HIV. Results Of 907 PLWH diagnosed between 2011 and 2019, 522 (58%) had ≥ 1 healthcare contact at any level between HIV acquisition and > 30 days before diagnosis. At least one European Centre for Disease Prevention and Control (ECDC) indicator condition was recorded for 119 (23% of 522), and 112 (21%) were born in a high-prevalence country. In total, 384 of 907 (42%) had visited a PHC physician, and 58% of those with CD4+ T-cell count  30 days before diagnosis, 18% with ≥ 1 ECDC indicator condition, and 367 (18%) had been hospitalised, 20% with ≥ 1 ECDC indicator condition. The most common ECDC indicator conditions > 30 days before diagnosis at all levels of healthcare were pneumonia, sexually transmitted infections, unexplained fever, herpes zoster, pregnancy and lymphadenopathy. Conclusion We recommend enhancing indicator condition-based HIV testing by all healthcare providers, particularly for gonorrhoea, syphilis and, for persons younger than 50 years, also herpes zoster and lymphadenopathy.